Micropropagation and Assessment of Genetic Stability of In Vitro Raised Jojoba (Simmondsia chinensis Link.) Plants Using SCoT and ISSR Markers (Plant Tissue Culture and Biotechnology, 2016)
This study is aimed at developing an efficient method for micropropagation of true-to-type jojoba plants. Nodal segments were used for in vitro shoots proliferation. Among three concentrations of BA used for multiplication, 1 mg/l BA gave the highest number of shoots. To enhance growth of shoots, combinations of BA and Kn were investigated. The greater value of shoot length and the maximum number of nodes were observed in the medium containing 1 mg/l BA + 1.5 mg/l Kn. Among different medium used to increase the rate of multiplication, the maximum number of shoots was recorded at ½ MS + Gamborg B5 (B5) vitamins + 2 mg/l Kn + 10 mg/l adenine sulphate (AS). Rooting was obtained upon supplementation of ½ Woody Plant Medium (WPM) with 1 mg/l IBA. Acclimation was achieved by transplanting rooted plantlets into pots containing peat moss and vermiculite. Start codon targeted (SCoT) and intersimple sequence repeat (ISSR) analyses were carried out to assess the genetic fidelity of micropropagated plantlets. All banding profiles of the two analyses from micropropagated plants were monomorphic and similar to the mother plant. Hence, this protocol can be employed for commercial micropropagation of jojoba without the risk of losing genetic stability.Plant Tissue Cult. & Biotech. 25(2): 165-179, 2015 (December)